Persepsi Guru IPA terhadap Praktek Asesmen Diagnostik untuk Memetakan Kendala Belajar Siswa SMP pada Implementasi Pembelajaran Mendalam - Taftazani Nurul Izzati; Mobinta Kusuma; Fahmi Fatkhomi; Muriani Nur Hayati (Mataram University, 2026)
This research aims to describe and analyze science teachers' perceptions of diagnostic assessment practices and their utilization in mapping student learning constraints during the implementation of the deep learning approach. The study employed a qualitative approach with a phenomenological design. The research subjects consisted of five science teachers at SMP Negeri 2 Warureja, selected based on their diverse teaching experiences. Data collection techniques included in-depth interviews, non-participant observation, and literature study. Data analysis was systematically conducted using NVivo 12 software through open coding, axial coding, and selective coding stages. The results indicate that science teachers possess positive perceptions and high pedagogical awareness of the urgency of diagnostic assessment in preventing misconceptions and mapping learning readiness. However, its implementation faces significant structural barriers, including limited time, heavy teaching loads (6–10 classes per teacher), administrative burdens, and technical doubts regarding independent instrument development. As a form of creative negotiation, teachers utilize assessment results to form heterogeneous learning groups with peer tutoring systems and adapt teaching strategies through the use of digital media (Google Forms/Quizizz) and contextual approaches. This study concludes that diagnostic assessment serves as a crucial bridge toward deep learning, yet its effectiveness depends heavily on the teachers' ability to navigate systemic constraints in the field. It is recommended that policies be established to reduce teaching loads and provide sustainable technical assistance for teachers to optimize assessment practices.